2020
DOI: 10.1371/journal.pone.0241837
|View full text |Cite
|
Sign up to set email alerts
|

Relative expression of microRNAs, apoptosis, and ultrastructure anomalies induced by gold nanoparticles in Trachyderma hispida (Coleoptera: Tenebrionidae)

Abstract: The extensive use of nanomaterials generates toxic effects on non-target species and the ecosystem. Although gold nanoparticles (Au-NPs) are generally expected to be safe, the recent study contains conflicting data regarding their cytotoxicity in the darkling beetles Trachyderma hispida. The study postulated cellular perturbation in the ovarian tissue of the beetles induced by a sublethal dose of Au-NPs (0.01 mg/g). When compared with the controls, a significant inhibition in the activities of the antioxidant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 62 publications
1
6
0
1
Order By: Relevance
“…The emergence of apoptotic cells verifies the findings of the comet assay. Our findings are consistent with those of El-Ashram et al 16 , who found an abnormality in the oogenesis with Au exposure in Trachyderma hispida . Nuclear deformities are the first symptoms of cell death 49 , which are evident in the trophocytes in this study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The emergence of apoptotic cells verifies the findings of the comet assay. Our findings are consistent with those of El-Ashram et al 16 , who found an abnormality in the oogenesis with Au exposure in Trachyderma hispida . Nuclear deformities are the first symptoms of cell death 49 , which are evident in the trophocytes in this study.…”
Section: Discussionsupporting
confidence: 93%
“…In our recent studies, we highlighted a strong and consistent association between exposure to Ag-NPs and the structural and physiological alterations, even at the molecular and transcriptional level of insect gonads in darkling beetles ( Blaps polychresta ). However, it is well known that females are more susceptible to the toxicity of nanoparticles due to great variations in physiological functions 1 , 16 , 17 . A few recently published studies delineated the importance and potential exploitation of female beetles as nanotoxicity indicator species 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the UV-Vis absorption spectra were precisely determined by an Ocean Optics USB 2000 + VISNIR fiber optical spectrophotometer. This commercially supplied AgNPs produced by NanoTech Egypt was previously characterized in several publications using spectrophotometric assays, transmission electron microscopy, FTIR, and XRD (Abou Elez et al 2021 ; El-Ashram et al 2020 ; Fouad et al 2021 ; Ouf et al 2017 ). The AgNPs exhibited a spherical shape with an average diameter of 20 ± 5 nm and it was dispersed in deionized water (DW) (Abou Elez et al 2021 ; El-Ashram et al 2020 ; Fouad et al 2021 ; Ouf et al 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…This commercially supplied AgNPs produced by NanoTech Egypt was previously characterized in several publications using spectrophotometric assays, transmission electron microscopy, FTIR, and XRD (Abou Elez et al 2021 ; El-Ashram et al 2020 ; Fouad et al 2021 ; Ouf et al 2017 ). The AgNPs exhibited a spherical shape with an average diameter of 20 ± 5 nm and it was dispersed in deionized water (DW) (Abou Elez et al 2021 ; El-Ashram et al 2020 ; Fouad et al 2021 ; Ouf et al 2017 ). The absorption spectrum of the AgNPs displayed a peak at 410 nm (Abou Elez et al 2021 ; El-Ashram et al 2020 ; Fouad et al 2021 ; Ouf et al 2017 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation